2008 IEEE International Symposium on Information Theory 2008
DOI: 10.1109/isit.2008.4595134
|View full text |Cite
|
Sign up to set email alerts
|

Improving LZ77 bit recycling using all matches

Abstract: There exist lossless compression techniques, such as LZ77, that have the particularity that some original file may be compressed in more than one way, e.g. by choosing other matches than the closest longest ones only. The existence of multiple encodings per original file causes redundancy, i.e. it tends to make compressed files longer than necessary, on average. Recently, a technique called bit recycling was introduced to help reduce the redundancy caused by the multiplicity of encodings. It has been used to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…The side-channel is general purpose and it may carry any useful data. In previous work, it has been used for information hiding, or steganography [2], for authentication [1], for error detection or correction [9], and for bit recycling [4], [6], [13]. This last application is described in greater detail next.…”
Section: Data Embedding Via Match Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The side-channel is general purpose and it may carry any useful data. In previous work, it has been used for information hiding, or steganography [2], for authentication [1], for error detection or correction [9], and for bit recycling [4], [6], [13]. This last application is described in greater detail next.…”
Section: Data Embedding Via Match Selectionmentioning
confidence: 99%
“…Bit recycling aims at improving the rates achieved by compression techniques, such as LZ77 [14], that suffer from the redundancy caused by the multiplicity of the encodings [4], [6], [13]. Bit recycling takes the pragmatic approach of detecting and exploiting the multiplicity in order to recover a compensation instead of trying to eliminate the multiplicity at the source (e.g., Kawabata's approach for LZ77 [8]).…”
Section: Introductionmentioning
confidence: 99%
“…It turned out that bit recycling was able to achieve better compression by exploiting the multiplicity of encoding feature rather than systematically selecting the shortest codeword. Variants of bit recycling have been applied on LZ77 algorithm in [6] and [8], the experimental results of [7] showed that bit recycling has achieved a reduction of about 9% in the size of files that has been compressed by Gzip [9]. The authors of bit recycling have pointed out that their technique could not minimize the redundancy perfectly since it is built on Huffman coding [10], which does not have the ability to deal with codewords of fractional lengths, i.e.…”
Section: Introductionmentioning
confidence: 99%